An efficient scenario-based stochastic programming for optimal planning of combined heat, power, and hydrogen production of molten carbonate fuel cell power plants. (1st April 2015) - Bornapour, Mosayeb; Hooshmand, Rahmat-Allah
Abstract: In this paper, a stochastic model is proposed for planning the location and operation of Molten Carbonate Fuel Cell Power Plants (MCFCPPs) in distribution networks when used for Combined Heat, Power, and Hydrogen (CHPH) simultaneously. Uncertainties of electrical and thermal loads forecasting; the pressures of hydrogen, oxygen, and carbon dioxide imported to MCFCPPs; and the nominal temperature of MCFCPPs are considered using a scenario-based method. In the method, scenarios are generated using Roulette Wheel Mechanism (RWM) based on Probability Distribution Functions (PDF) of input random variables. Using this method, probabilistic specifics of the problem are distributed and the problem is converted to a deterministic one. The type of the objective functions, placement, and operation of MCFCPPs as CHPH change this problem to a mixed integer nonlinear one. So, multi-objective Modified Firefly Algorithm (MFA) and Pareto optimal method are employed for solving the multi-objective problem and for compromising between the objective functions. During the simulation process, a set of non-dominated solutions are stored in a repository. The 69-bus distribution system is used for evaluating the proper function of the proposed method. Highlights: A scenario-based stochastic programming is proposed for optimal planning of Molten Carbonate Fuel Cell Power Plants (MCFCPP). The effect of Combined Heat, Power, and Hydrogen production (CHPH) is considered simultaneously. Uncertainties of electrical and thermal loads forecasting are considered. Uncertainties of the pressures of H2, O2 and CO2 importing to MCFCPP, and the nominal temperature of MCFCPP are considered. Generation of thermal energy, hydrogen, and total emission of MCFCPPs and network are managed.